Environmental policy change in emerging market democracies: Central and Eastern Europe and Latin America compared - Tosun, Jale (University of Toronto Press, 2013)
"This book examines environmental policy change in twenty-eight Central and Eastern European and Latin American countries against a background of significant political and economic transformation over the past two decades. Through cross-regional comparison and a multi-methods approach, Jale Tosun investigates changes in the regulation of air, soil, and water pollution, genetically modified corn, and the sustainable management of forests. Tosun also looks at the relationship between system transformation and the creation of environmental procuracies in both parts of the world
Includes bibliographical references and index
Keywords: Central Europe; Eastern Europe; Latin America; Electronic books; Lateinamerika; Osteuropa; Mitteleuropa; Umweltpolitik